Why is it necessary media education? An analysis of case by the film Cobardes - María Marcos Ramos (Ediciones Universidad de Salamanca, 2012)
The present article tries to demonstrate why is need to incorporate media education into the curriculum so that students can apply when they consume content media. It has been used for research on a film directed at teenagers, Cobardes (Juan Cruz y José Corbacho, 2008), and analyzed post in relation to violence. Through a survey and analyzing the results with the help of statistics, it has been shown that, although it is a movie recommended for over 13 years, is required viewing with parental or school mediation.